2020
DOI: 10.1021/acs.jpcc.0c03508
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Oxygen Activation at a Conducting Polymer: Electrochemical Oxygen Reduction Reaction at PEDOT Revisited, a Theoretical Study

Abstract: Molecular oxygen requires activation in order to be reduced, which prompts extensive searching for efficient and sustainable electrode materials to drive electrochemical oxygen reduction reaction (ORR), of primary importance for energy production and storage. A conjugated polymer PEDOT is a metal-free material for which promising ORR experimental results have been obtained. However, sound theoretical understanding of this reaction at an organic electrode is insufficient, as the concepts inherited from electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 71 publications
(123 reference statements)
0
47
0
Order By: Relevance
“…One possible source of these parasitic reactions is the reduction of dissolved oxygen by dedoped PEDOT 0 to form H 2 O 2 . 21,42 Other factors include possible changes in the PSS binding site local environment that might occur during doping/dedoping, resulting in changes in  Since the measured residual value of , 〈 ̅ 〉, is also affected by the shape of the PEDOT-rich domains (as illustrated in Figure S12), the hysteresis may be caused by microstructural changes of the PEDOT:PSS (quantified via the order parameter, S) during electrochemical biasing, such as film swelling due to changes in water content. Other phenomena might be important: for example, Paulsen et al 43 recently reported an unsymmetric rate of structural change of PEDOT:PSS during doping and dedoping by operando X-ray scattering, ascribing the transient structural behaviour to the complex polaron-bipolaron dynamics that affects electronic charge carrier dynamics.…”
Section: Origin Of the Hysteresismentioning
confidence: 99%
“…One possible source of these parasitic reactions is the reduction of dissolved oxygen by dedoped PEDOT 0 to form H 2 O 2 . 21,42 Other factors include possible changes in the PSS binding site local environment that might occur during doping/dedoping, resulting in changes in  Since the measured residual value of , 〈 ̅ 〉, is also affected by the shape of the PEDOT-rich domains (as illustrated in Figure S12), the hysteresis may be caused by microstructural changes of the PEDOT:PSS (quantified via the order parameter, S) during electrochemical biasing, such as film swelling due to changes in water content. Other phenomena might be important: for example, Paulsen et al 43 recently reported an unsymmetric rate of structural change of PEDOT:PSS during doping and dedoping by operando X-ray scattering, ascribing the transient structural behaviour to the complex polaron-bipolaron dynamics that affects electronic charge carrier dynamics.…”
Section: Origin Of the Hysteresismentioning
confidence: 99%
“…[ 9 ] Upon incorporation of redox receptors or selective membranes, OECTs demonstrate sensitive detection of specific metabolites [ 10–13 ] and ions [ 14,15 ] in aqueous media and are desirable as miniaturized marine sensors. However, for analytes with high redox potentials such as dissolved oxygen, [ 16 ] the large voltage required to drive the sensing reaction may inherently alter the chemical composition of the semiconductor within the OECT channel and degrade device performance. [ 17,18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Amongst the conducting polymers, poly (3,4-ethylene dioxythiophene) (PEDOT) is the most investigated for ORR. [8][9][10][11][12] The inherent advantage of this material contributes to its high chemical stability, high mechanical flexibility, and its unique-combined electric and ionic conductivity. [13] Furthermore, PEDOT : PSS swells in aqueous media, forming a permeable 3D network enabling the coincidence of electrons, ions and reacting molecules.…”
Section: Introductionmentioning
confidence: 99%